Orthosiphon aristatus leaf extracts as α-glucosidase and soybean lipoxygenase inhibitors and their toxicity: in-vitro and in-silico approaches - Ahda, Mustofa; Ahmed, Qamar Uddin; Utami, Dwi; Mahfudh, Nurkhasanah; Syahputra, Ryan; Anwar, Muslih; Hernawan, Hernawan; Hanifah, Dini; Zainal Fithri, Helmi Husaini; Abdul Hamid, Azzmer Azzar; Rofiee, Mohd Salleh; Jaswir, Irwandi; et al. (Springer Nature, 2025)
An in silico approach for identifying potential bioactive compounds in Orthosiphon aristatus (Blume) Miq., Lamiaceae, leaf extracts presents a cost-effective strategy for early-stage drug discovery. This study aimed to profile selected compounds from O. aristatus leaf extracts using LC-HRMS analysis and evaluated their inhibitory potential against α-glucosidase and soybean lipoxygenase (sLOX). The aqueous extract exhibited stronger α-glucosidase inhibition compared to the ethanolic extract. Both extracts showed notable inhibitory activity against sLOX, supported by findings from in vitro and in silico assays. Molecular docking revealed that compounds such as eupatorin (ΔG−8.9 kcal/mol), 3,5-dihydroxy-4′,7-dimethoxyflavone (ΔG−8.3 kcal/mol), aurantioobtusin (ΔG−8.3 kcal/mol), rosmarinic acid (ΔG−8.6 kcal/mol), 5β-cholestane-3α,7α,12α,26- tetrol (ΔG−9.0 kcal/mol), and kukoamine A (ΔG−7.8 kcal/mol) interacted with the catalytic residues of α-glucosidase via hydrogen bonding. Compounds inhibiting sLOX, including aurantioobtusin (ΔG−9.4 kcal/mol), 3,5-dihydroxy-4′,7- dimethoxyflavone (ΔG−9.8 kcal/mol), rosmarinic acid (ΔG−9.6 kcal/mol), and kukoamine A (ΔG−8.8 kcal/mol), were predicted to bind within the quercetin-binding region of the enzyme’s allosteric site. Furthermore, ADME predictions suggested favourable pharmacokinetic profiles, including high absorption, good water solubility, and low toxicity. Toxicity assessment indicated that the aqueous extract was less toxic, containing only one identified toxic compound. Nevertheless, zebrafish embryo exposure at 800 µg/ml resulted in developmental abnormalities, such as reduced pigmentation, yolk sac edema, spinal curvature, and cardiac edema. Overall, the study demonstrates that in silico methods effectively complement in vitro analyses in profiling bioactive compounds from O. aristatus, reinforcing the plant’s therapeutic potential as a natural source of α-glucosidase and sLOX inhibitors.